The Committed of the Auditors for the Procedures of Environmental audits (An Exploratory Study of a sample of auditing offices in Iraq) - جيجان حذام فالح (Journal of Economics and Administrative Sciences, 2016)
At the beginning of the nineties increased responsibility of the auditor to the community as the demand for auditing the environmental performance for the economic units in addition to audit the financial performance. With the aim of preserving the environment and reducing the damagse as aresult of the negative effects of the activities of these units. The researh deal with two sides the first one identifies the theoretical framework of the concept of environmental audits, requirements, methods, types of procedures, and duties of the auditor in conducting environmental audits. It also deals with the concept of the environmental report and the elements that should be included in the report itself, as well as the role of local and international organizations in practicing the environmental auditing. The second side has tested the research hypotheses by preparing a questionnair distributed to a sample of the study community ,which included auditing offices . The questionnaire contains two sides, the first one is to test the reality of the application of auditing offices for the concept of environmental audits, extent of their commitment to environmental audit procedure recently .The second to test the commitment of the auditing offices in Iraq to the environmental audit procedures to protect the environmental in the future. It includes three axis (environmental compliance test,the test of laboratory technical testing, financial and environmental analysis). The results were analyzed using the( SPSS ) statistical program, the study concluded that the auditing offices in Iraq does not currently commit to the environmental audit procedures. It also concluded that the commitment of auditing offices to the environmental procedures in Iraq in the future will contribute in protecting environment. Also The study also recommended the need for state intervention to issue laws and regulations relating environmental audit, and to put bases for granting Iraq Vocational certification that enable the auditor to conduct environmental audit profession. Key wards: Environmental Audit , Enviro